Teknologi dan Inovasi dalam Pendidikan Islam: Perspektif Etika Islam dan Tantangan Globalisasi di Era Digital - Nikmatul Khoiriah; Darwis Hude (Irsyaduna: Jurnal Studi Kemahasiswaaan, 2025)
This study aims to analyze the utilization of technology and educational innovation in Islamic education from the perspective of Islamic ethics and the challenges of globalization in the digital era. The study employs a qualitative-descriptive approach using library research, drawing on primary Islamic sources, including the Qur’an, Hadith, and classical as well as contemporary tafsir, alongside secondary sources such as academic books and peer-reviewed journal articles. The findings indicate that educational technology exhibits an ambivalent nature. On the one hand, technology enhances learning effectiveness, expands educational access, and enriches instructional methods in Islamic education. On the other hand, the use of technology without a solid Islamic ethical framework may weaken moral development, diminish educators’ role as moral exemplars, and lead to value disorientation among students. This study emphasizes that the integration of Islamic ethical principles such as honesty (ṣidq), responsibility (amānah), and self-restraint (‘iffah) is essential in guiding the use of educational technology. Furthermore, the concept of Islamization of technology is proposed as a strategic approach to ensure that educational innovation does not merely focus on technical efficiency or secular objectives, but remains aligned with the goals of maqāṣid al-sharī‘ah. In this context, educational technology is expected to function as a means of strengthening morality, spirituality, and the holistic formation of insan kamil in the digital age.